Keeping Legislators Informed: The University of Manitoba Study - Jones, Glen A. (Canadian Journal of Higher Education, 1991)
Universities attempt to influence government policy through the input of interests to the political process. Given the importance of keeping legislators informed of university interests and activities, a study was conducted in 1986 to obtain data from Members of the Manitoba Legislative Assembly on the adequacy of information provided by the University of Manitoba. The purpose of this paper is to report the major findings of that study, including the types of information requested by legislators, and to discuss three themes which emerged from the interviews: that the University should move slowly in its attempts to improve relations with legislators, that secondary relations should be strengthened, and that the University should present its case in a more positive fashion.